2020
DOI: 10.1111/evj.13214
|View full text |Cite
|
Sign up to set email alerts
|

Application of droplet digital PCR in diagnosing of X monosomy in mares

Abstract: Background X monosomy is the most common disorder of sex development in horses. Although cytogenetic analysis is still the gold standard in the diagnosis of equine X monosomy, novel molecular techniques are being sought to quickly and reliably detect this chromosome abnormality. Objectives The goal of this study was to evaluate the usefulness of a novel variant of the PCR technique—namely, droplet digital PCR (ddPCR)—in the detection of X monosomy in mares. Study design A proof of concept of the usefulness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…In addition, the results obtained in male-female chimeras demonstrate that SNP-CNA analysis can also detect individuals carrying ECAX mosaicisms. This is an important point considering that 63,X/64,XX, the third most important sex-pair chromosomal alteration reported in this species (Bugno et al 2001), cannot be detected by using the molecular methods currently available (Anaya et al 2017;Szczerbal et al 2020). However, all the chimeric samples analyzed in this study showed similar percentages of each cell line (64,XX or 64,XY in this case).…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…In addition, the results obtained in male-female chimeras demonstrate that SNP-CNA analysis can also detect individuals carrying ECAX mosaicisms. This is an important point considering that 63,X/64,XX, the third most important sex-pair chromosomal alteration reported in this species (Bugno et al 2001), cannot be detected by using the molecular methods currently available (Anaya et al 2017;Szczerbal et al 2020). However, all the chimeric samples analyzed in this study showed similar percentages of each cell line (64,XX or 64,XY in this case).…”
Section: Discussionsupporting
confidence: 48%
“…Copy number alterations in horses have been diagnosed using different approaches, including karyotyping (Neuhauser et al 2019), in situ hybridization (Bugno et al 2007b), short tandem repeat (STR) allele counting using standard (Demyda-Peyrás et al 2014) or specific panels (Anaya et al 2017), and, more recently, droplet digital PCR (Szczerbal et al 2020). These techniques are expensive and/ or highly specific to a particular syndrome, making their integration into routine screening problematic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2019; Szczerbal et al . 2020). The main goal of this study was thus to assess the usefulness of droplet digital PCR (ddPCR) in precise genotyping of equine STX17 4.6‐kb duplication, and to screen for its potential wider copy‐number variation in a panel of gray and nongray horses of various breeds.…”
Section: Figurementioning
confidence: 99%
“…This increased prevalence observed, in comparison with other livestock species, is quite remarkable and mainly due to the complexity of the horse karyotype and the lack of availability of equine cytogenetic laboratories in several countries [42]. However, new genomic technology, based on short tandem repeats (STRs) [43], droplet digital PCR (ddPCR) [44], and, more recently, single nucleotide polymorphism (SNP) genotyping array [45], is being constantly developed. There is, therefore, likely to be an increase in the number and complexity of chromosomal syndromes associated with infertility detected in horses in the near future.…”
Section: Copy Number Abnormalities and Fertility: The Role Of The Sexmentioning
confidence: 99%